PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN DAN KEBIJAKAN HUTANG TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI MEDIASI - Albert Marido Agustianto; Herman Ruslim; Jonnardi; MF Djeni Indrajati (Jurnal Kontemporer Akuntansi, 2024)
This study aims to analyze the effect of profitability, company growth, and debt policy on stock prices with dividendpolicy as a mediating variable. This study uses a quantitative method by taking a population of companies listed onthe Indonesian Stock Exchange (IDX) in the consumer goods sector. The sample was selected by purposive samplingtechnique in order to obtain a sample of 24 companies. The data analysis method used is structural equation modelanalysis using the PLS SEM test tool. The results showed that profitability, company growth, and debt policy had nosignificant effect on stock prices. The results of the mediation test show that dividend policy is not proven as amediating variable for the effect of profitability, company growth, and debt policy on stock prices. Based on theresults of the different test, it shows that there is a significant difference in the stock prices of consumer goodscompanies before and during the Covid-19 pandemic